Design of measuring flow velocity device for liquid fluid with venturi meter principles based on Arduino - Rendi Hadi Perdana; Nur Aji Wibowo; Made R. S. S. N. Ayub (Journal of Science and Science Education, 2018)
Fluid flow velocity in physics can be found on the principle of venturi meter. The Fluid flow concept is easy to understand if visualized. We need a learning media of fluid velocity, so the concept can understanding. Design of this tool aims to help students understand the fluid flow velocity. Data is taken automatically by Arduino-based water flow sensor, with speed change at the speed knop. Based on the design result of the tool which can be obtained by measuring the fluid flow velocity at a speed greater than 0.36 m/s, and proved by graph analysis logarithmic between velocity values of magnitude theory (Vtheory = 0.5x + 0.7934 m/s ) and tool speed (Vtool = 0.5825x + 1.129 m/s). The speed difference between the theory and the tool indicates the magnitude of the frictional speed due to the turbulent flow. So it can be concluded the design of this tool can be used as a learning media to help students in understanding the topic of fluid.